2022
DOI: 10.1038/s41598-022-12385-0
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and remodeling pathways and risk of cardiovascular events in patients with ischemic heart failure and reduced ejection fraction

Abstract: Patients with heart failure (HF) and coronary artery disease (CAD) have a high risk for cardiovascular (CV) events including HF hospitalization, stroke, myocardial infarction (MI) and sudden cardiac death (SCD). The present study evaluated associations of proteomic biomarkers with CV outcome in patients with CAD and HF with reduced ejection fraction (HFrEF), shortly after a worsening HF episode. We performed a case–control study within the COMMANDER HF international, double-blind, randomized placebo-controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…A matched case–control study evaluated the association of proteomic biomarkers with CV outcomes in 455 controls and 485 cases with CAD and HFrEF after an episode of worsening HF [ 85 ]. A total of 276 plasma proteins were analyzed, resulting in 49 proteins significantly associated with clinical outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A matched case–control study evaluated the association of proteomic biomarkers with CV outcomes in 455 controls and 485 cases with CAD and HFrEF after an episode of worsening HF [ 85 ]. A total of 276 plasma proteins were analyzed, resulting in 49 proteins significantly associated with clinical outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of these proteins had an adjusted false discovery rate < 0.001: BNP, NT-proBNP, FGF23, growth differentiation factor 15 (GDF15), T-cell immunoglobulin, and mucin domain containing 4 (TIMD4), spondin 1 (SPON1), and pulmonary surfactant-associated protein D (PSP-D). Neither of these proteins were associated with individual clinical events (HF hospitalization, sudden cardiac death, and combined MI or stroke) [ 85 ]. Therefore, these proteins were considered strong but indiscriminate predictors of diverse CV events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry-(MS) based proteomics has the unique advantage of being unbiased and quantitative. Previous reported work suggest that large-scale proteomics analysis is a promising way of discovering novel biomarkers that could substantially improve the prediction of Alzheimer's disease, 24,25 ischemic stroke, 26,27 and cancer. 28 Furthermore, the importance of sufficiently large discovery cohorts has become increasingly evident.…”
Section: Proteomicsmentioning
confidence: 99%
“…However, excessive inflammation induces an unpredicted increase in inflammatory mediators, such as cytokines (tumor necrosis factor-α (TNF-α), interleukins, inducible nitric oxide synthase (iNOS)), chemokines, and reactive oxygen species (ROS). Inflammatory mediators have implications in heart disease (ischemic heart failure and cardiac ischemia/reperfusion injury) [ 1 , 2 ], brain disorders (depression and anxiety) [ 3 , 4 ], and lung disease (chronic obstructive pulmonary disease and acute lung injury) [ 5 , 6 ]. Recent studies have confirmed that ROS could also cause oxidative stress, leading to the activation of inflammatory pathways, the stimulation of macrophage polarization, and the triggering of cell damage [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%